Evaluating patients’ expectations from a novel patient-centered perspective predicts knee arthroplasty outcome - Filbay, S; Judge, A; Delmestri, A; Arden, N (Elsevier, 2018)
Background One in five patients are dissatisfied following knee arthroplasty and <50% have fulfilled expectations. The relationship between knee-arthroplasty expectations and surgical outcome remains unclear. Purpose Are expectations regarding the impact of pain on life after knee arthroplasty predictive of one-year outcome? Does the impact of pain on preoperative quality of life (QOL) influence this relationship? Methods Longitudinal cohort study of 1044 uni-compartmental (43%) or total knee-arthroplasty (57%) (UKA or TKA) patients, aged mean 69±9 years. Preoperatively, patients reported the impact of pain on QOL and the expected impact of pain on life one-year post-arthroplasty (none, mild, moderate/severe/extreme). One-year postoperative outcomes: non-return to desired activity (specific activities were specified preoperatively), surgical dissatisfaction, not achieving Oxford Knee Score (OKS) minimal important change (MIC). Logistic regression including covariates was performed for all patients and subgroups (better vs. worse pre-operative pain-related QOL; UKA vs. TKA; osteoarthritis indication vs. other indication). Results Expecting moderate-to-extreme pain (vs. no pain) predicted non-return to activity (odds ratio (95% CI), 2.3(1.3, 4.1)), dissatisfaction (4.0(1.7, 9.3)), and not achieving OKS MIC (3.1(1.5, 6.3)). Expecting mild pain (vs. no pain) predicted worse outcomes for patients with better preoperative pain-related QOL (non-return to activity: 2.7(1.5, 4.8), not achieving OKS MIC: 2.5(1.1, 5.5)). Expecting moderate-to-extreme pain (vs. no pain) predicted worse outcomes for patients with worse preoperative pain-related QOL (non-return to activity: 2.4(1.1, 5.5), dissatisfaction: 5.0(1.7, 14.8), not achieving OKS MIC: 3.4(1.4, 8.6)). The odds of a poor outcome in people with worse expectations was higher for UKA patients. Conclusions Expecting a worse outcome predicted surgical dissatisfaction, less clinical improvement and non-return to desired activity. Patients expecting a more optimistic outcome relative to preoperative status achieved better surgical outcomes.